Horizontal Collaboration in Crisis Management: An Experimental Study of the Duty Officer Function in Three Public Agencies. Issue 4 (23rd September 2019) - Deverell, Edward; Alvinius, Aida; Hede, Susanne
Abstract : Lately, scholars have been engaging in studies on the crossroads between collaborative public management and crisis management, but our knowledge on how organizations work together with interorganizational goals in times of crisis or in relation to the threat that crises pose, is still limited. This study aims to illuminate how interagency horizontal collaboration plays out in practice. An interview study with twenty‐three Swedish duty officers in three organizations with critical tasks in the institutional crisis management system is carried out to unearth impediments to interagency collaboration that emerge when organizations from different policy subsystems engage in crisis collaboration. Empirically, the study contributes with new knowledge on how a crucial function in crisis management carries out work and deals with challenges. Theoretically, it contributes to the literature on crisis management collaboration by shedding light on processes of horizontal collaboration in the area of crisis management. 危机管理中的横向协作：关于三个公共机构中值勤官职能的实验研究: 近期，学者一直致力研究协作式公共管理和危机管理的共同之处，但各机构如何在危机期间，或由危机引起的威胁期间，就组织间目标进行相关合作，这方面的知识还很匮乏。本研究致力阐明机构间的横向协作如何在实践中发挥作用。针对三个机构中负责机构危机管理体系的关键任务的23名瑞典值勤官进行了面谈研究，以找出来自不同政策子系统的机构在参与危机协作时机构间协作出现的障碍。实证上，本研究通过提供有关危机管理中关键职能如何开展工作、应对危机的新知识，对学术做出了贡献。理论上，本研究通过阐明危机管理领域中横向协作的过程，进而促进了有关危机管理协作的文献。 Colaboración horizontal en la gestión de crisis: un estudio experimental de la función de oficial de turno en tres agencias públicas: Últimamente los académicos han estado trabajando en estudios de la yuxtaposición entre la gestión pública colaborativa y la gestión de crisis, pero nuestro conocimiento de cómo las organizaciones trabajan juntas con metas interorganizacionales en tiempos de crisis o en relación a la amenaza que representan las crisis es todavía limitado. Este estudio busca ilustrar cómo la colaboración horizontal inter agencia se desarrolla en la práctica. Se lleva a cabo un estudio con entrevistas a veintitrés oficiales de servicio suecos en tres organizaciones con tareas críticas en el sistema institucional de gestión de crisis para descubrir los impedimentos a la colaboración entre agencias que surgen cuando organizaciones de diferentes subsistemas de políticas participan en la colaboración en crisis. Empíricamente, el estudio contribuye con nuevos conocimientos sobre cómo una función crucial en la gestión de crisis lleva a cabo el trabajo y aborda los desafíos. Teóricamente, contribuye a la literatura sobre colaboración en gestión de crisis al ilustrar los procesos de colaboración horizontal en el área de gestión de crisis.